Povoar e enquadrar - Maria Filomena Andrade; João Luís Fontes (Medievalista)
The Christian conquest of Lisbon, in 1147, initiated a new era in the city which immediately saw diocesan life restored and parish life quickly revived. Efforts to secure the settlement and ecclesiastical accommodation of the urban population went hand-in-hand with the gradual establishment in the city of various religious orders, some drawing upon previous eremitic experiences, others with a marked pastoral bias combining liturgy, preaching, and charitable acts. The very peculiar qualities of the city, possessed of an intense economic life, a growing population, a royal court that sojourned there with increasing regularity and for increasingly prolonged periods, attracted more and more people from diverse regions and stimulated the rapacity of noblemen and rich merchants who contributed to its rise as the capital city of the Kingdom. It also made Lisbon particularly attractive to the religious orders who, between them, contested the urban space, its populations, and its resources. This article seeks to explain this process of establishment and articulation of convents and monasteries from the time of the Christian conquest to the fourteenth century, and to contextualise it within the intense urban life of the city of Lisbon.